Feminism in Education Management - Zetty Karyati (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to obtain an overview of the progress of feminism in educational management. This study uses a qualitative descriptive approach, with the method of literature. Qualitative descriptive research approach is research that is used for the purpose of providing a qualitative description of the phenomenon or event being studied. Research with the library method is a theoretical study, references, and other scientific literature related to the culture, values, and norms that develop in the social situation under study. From this study, it was found that there are still gaps between women and men, both in terms of education and in terms of occupying job positions in education management. In other words, feminism still needs a long process to be said to have succeeded in achieving its goals.